NZ J Ecol 2016
DOI: 10.20417/nzjecol.40.43
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity and risk to lizards of rodenticides and herbicides commonly used in New Zealand

Abstract: Invasive species can have negative consequences on native reptile populations, especially on island systems. Chemical control can be a cost-effective way to control or eradicate invasive species. Chemical control is currently in use in New Zealand to limit impacts of non-native mammals and plants on a range of native biodiversity. However, it is important to consider the potential non-target risks of chemical control to native species that are likely already significantly reduced in number. We aimed to charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…In highly detailed studies, Weir et al (2015) reported that brodifacoum administered orally (capsule) or applied dermally (neat material placed on dorsal surface and covered with an occlusive bandage) to Western fence lizards (Sceloporus occidentalis) did not evoke signs of intoxication at doses ranging up to 1750 mg/kg. Using similar methods, the acute oral median lethal dose for coumatetralyl exceeded 1750 mg/kg, for diphacinone the LD50 was ~1750 mg/kg, and for pindone the LD50 was estimated to be 550 mg/kg (Weir et al 2016). Thus, the LD50s for coumatetralyl, diphacinone, pindone and brodifacoum in Western fence lizards exceeded laboratory rodent values by one to two orders of magnitude.…”
Section: Acute Oral Toxicity Studiesmentioning
confidence: 93%
See 1 more Smart Citation
“…In highly detailed studies, Weir et al (2015) reported that brodifacoum administered orally (capsule) or applied dermally (neat material placed on dorsal surface and covered with an occlusive bandage) to Western fence lizards (Sceloporus occidentalis) did not evoke signs of intoxication at doses ranging up to 1750 mg/kg. Using similar methods, the acute oral median lethal dose for coumatetralyl exceeded 1750 mg/kg, for diphacinone the LD50 was ~1750 mg/kg, and for pindone the LD50 was estimated to be 550 mg/kg (Weir et al 2016). Thus, the LD50s for coumatetralyl, diphacinone, pindone and brodifacoum in Western fence lizards exceeded laboratory rodent values by one to two orders of magnitude.…”
Section: Acute Oral Toxicity Studiesmentioning
confidence: 93%
“…6). The limited data for reptiles (Brooks et al 1998;Weir et al 2015Weir et al , 2016 does not permit a generalized sensitivity comparison to higher vertebrates.…”
Section: Differences In Ar Sensitivity Among Taxamentioning
confidence: 99%
“…For each experiment, we used linear logistic regression to determine the 50% survival threshold in response to varying water and air temperature, with separate curves modelled for black and red mangroves from both BC and Florida. We chose a 50% threshold as it is widely used in the ecophysiology and toxicology fields to estimate population mortality rates after exposure to various abiotic stressors (Lagarto Parra et al, 2001;Randhawa, 2009;Weir et al, 2016).…”
Section: Analysis Of Air and Water Temperature Experimentsmentioning
confidence: 99%
“…The metabolic capacity of flufenoxuron in the tissues may be lower than that of diflubenzuron, which induced higher residua level at the end of exposure. Because of the lower metabolic rate of flufenoxuron, it may take longer for toxicity to occur in reptiles given the same dose (Weir et al, 2016). A previous study also suggested that the enhanced toxicity of flufenoxuron to Spodoptera littoralis compared with diflubenzuron may be attributed to its lower metabolism (Clarke and Jewess, 1990).…”
Section: Groupmentioning
confidence: 99%